Outcome of Allogeneic Hematopoietic Stem Cell Transplantation in Acute Myeloid Leukemias with Hyperdiploid Karyotype - TL Gindina; NN Mamaev; ES Nikolaeva; SN Bondarenko; OA Slesarchuk; AS Borovkova; SV Razumova; OV Pirogova; AL Alyanskii; LS Zubarovskaya; BV Afanas’ev (Клиническая онкогематология)
Aim. To evaluate the prognostic impact of the different cytogenetic characteristics, including the modal number, the number of chromosomal aberrations in a complex karyotype, and adverse chromosomal abnormalities (ACA) (–7/7q–, –5/5q–, –17/17p–, t(6;9)(p22;q34)) on the results of allogeneic hematopoietic stem cell transplantation (allo-HSCT) in patients with hyperdiploid acute myeloid leukemia (H-AML).